EVALUASI PENGELOLAAN RUMAH SUSUN SEDERHANA SEWA DI BAKALAN KRAPYAK KABUPATEN KUDUS ABSTRAK - siska hadiyana prasayuningtyas; SUWANTO ADHI; GHULAM DZUNUWANUS (Journal of Politic and Government Studies, 2016)
Population growth each year has increased while the very limited availability of land is even less to make the price of land to be very expensive , so it is not affordable to the people's purchasing power , especially among the middle class . Land can not be separated from human life , the function of soil is essential for humans , especially for land for housing . People really expect to buy land that will be built a house on the land . The price of land which annually increases make the land can not be bought by people, particularly the underprivileged ( poor ) . Seeing such conditions Kudus Regency Government makes program development modest apartment rental.The purpose of this study is to determine and describe the government's policy in relocating the community to the development of simple Flats Rent ( Rusunawa ) in the village of Bakalan Krapyak , Kaliwungu Kudus and to know The problems that arise in the relocation of the community and how the solution . This research is descriptive analytic research using qualitative approach . Data collection techniques by means of interviews with informants , the researchers also conducted direct observation penelkitian object and document the location of the relevant research is conducted with the actual situation.The results showed that in fact the flats built by the Holy District Government less demand by the public , especially people who occupy around the riverbanks Gelis . Found several weaknesses in relocating public policy program , which has not fulfilled rusunawa adequate facilities and the lack of public awareness about the environment . Construction of rental flats Bakalan Krapyak a logical consequence in the district of Kudus considering many slums and the limited ability of the local economy are low in building a house , then through the construction of towers is expected to overcome the problems hunia wild that the eviction of residents who inhabit the land unlicensed inevitable.Recommendations are given that in the implementation of the relocation program then should the parties involved to be responsive to the problems faced by the people being relocated, the entire process of the implementation of the relocation should be the aspirations of the displaced , and involving the community of preparation through the mechanism of a residential dwelling that is new , the realization of repair or Extra facilities Bakalan Rusunawa Krapyak that it is less, to be more comfortable for the occupants rusunawa and Kudus regency government must be firm in enforcing existing regulations , not to place among the violations of regulations proficiency level . Therefore there must be communication and coordination between levels of government involved in the enforcement of existing regulationsKeywords : Evaluation of Housing and Relocation Management Society.